Devising a method for improving pedestrian traffic safety when crossing railroad tracks by implementing an information system with a fixed warning time - Kovalchuk, Vitalii; Lesiv, Yulia (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is pedestrian safety when crossing railroad tracks at pedestrian crossings. A method for improving the safety of pedestrian traffic when crossing railroad tracks within the area approaching the railroad pedestrian crossing has been developed, by introducing an information system for warning pedestrians about train movement with a fixed warning time. Experimental measurements of the speed of the rolling stock were carried out in the area approaching the pedestrian crossing over the railroad track. With the mixed movement of trains, it was found that the lowest speed of the train was 67.46 km/h, and the highest was the passenger train – 131.9 km/h. At the same time, the speed of freight trains ranged from 74 to 79 km/h. Such data are needed to determine the speed of the rolling stock on the approach to the crossing or transition, which will allow the light and sound signal to be turned on in time when the movement of a pedestrian across the track will be dangerous. The methodology for calculating the length of the approach section to the pedestrian crossing, depending on the speed of the rolling stock, has been given. It was established that the speed of the rolling stock has a significant effect on the length of the approach section. At the lowest measured speed of the train – 67.46 km/h, the length of the approach section was 317.46 m, and when the passenger train was moving at a speed of 131.9 km/h – 620.68 m. For a single-track section of the railroad, a fixed time has been established for warning pedestrians about the approach of a train to the crossing. It is a constant value that is included in the warning information system on a single-track section, and after it, a complex light and sound alarm with an information board is activated, which will warn the pedestrian about the movement of the train. The method for improving the safety of pedestrian traffic with a fixed time of the pedestrian’s anticipation of the train movement could be used at crossings with pedestrian traffic, as a supplement to the crossing signaling subsystem in railroad transport. It can also be used at equipped pedestrian crossings over railroad tracks in urbanized areas. The advantage of introducing such a method is a fixed time to warn the pedestrian, in each specific case of the train approaching the crossing